"Internally Wicked": Investigating How and Why Essentialism Influences Punitiveness and Moral Condemnation. Issue 6 (25th June 2021) - Martin, Justin W.; Heiphetz, Larisa
Abstract: Kant argued that individuals should be punished "proportional to their internal wickedness, " and recent work has demonstrated that essentialism—the notion that observable characteristics reflect internal, biological, unchanging "essences"—influences moral judgment. However, these efforts have yielded conflicting results: essentialism sometimes increases and sometimes decreases moral condemnation. To resolve these discrepancies, we investigated the mechanisms by which essentialism influences moral judgment, focusing on perceptions of actors' control over their behavior, the target of essentialism (particular behaviors vs. actors' character), and the component of essentialism (biology vs. immutability). Participants punished people described as having a criminal essence more than those with a non‐criminal essence or no essence. Probing potential mechanisms underlying this effect, we found a mediating role for perceptions of control and weak influences of essentialism focus (behavior vs. character) and component of essentialism (biology vs. immutability). These results extend prior work on essentialism and moral cognition, demonstrating a causal link between perceptions of "internal wickedness" and moral judgment. Our findings also resolve discrepancies in past work on the influence of essentialism on moral judgment, highlighting the role that perceptions of actors' control over their behavior play in moral condemnation.